Vitamin A Inhibits Development of Dextran Sulfate Sodium-Induced Colitis and Colon Cancer in a Mouse Model. (19th May 2016) - Okayasu, Isao; Hana, Kiyomi; Nemoto, Noriko; Yoshida, Tsutomu; Saegusa, Makoto; Yokota-Nakatsuma, Aya; Song, Si-Young; Iwata, Makoto
Abstract : Vitamin A is essential to mucosal immunity and cell differentiation. The fact that lack of it might involve chronic inflammation and increased risk of cancer has been reported. Little is known about the mechanism of vitamin A deficiency in the development of colitis and its influence on development of colorectal cancer. To determine the influence of vitamin A deficiency on colitis and colorectal cancer development, an experimental study using a colitis mouse model was performed. Dextran sulfate sodium (DSS) colitis was induced in vitamin A-deficient and vitamin A-supplemented mice. Further, colorectal carcinoma was induced by a combination of azoxymethane preinjection and DSS colitis. Results were compared between the two groups mainly by immunohistochemical analysis. Colitis was more severe and recovery from colitis was slower in vitamin A-deficient mice than in vitamin A-supplemented mice. Compared with vitamin A-supplemented mice, vitamin A-deficient mice had decreases in colonic subepithelial myofibroblasts and the ratio of mucosal IgA + /IgG + cells, increases in CD11c + dendritic cells, and a higher rate of development of colorectal carcinoma with colitis following azoxymethane. Vitamin A lipid droplets in subepithelial myofibroblasts were decreased in vitamin A-deficient mice, suggesting alterations in colonic crypt niche function. Thus, vitamin A inhibited colitis and the development of colorectal cancer.